2020
DOI: 10.1016/j.conbuildmat.2020.120420
|View full text |Cite
|
Sign up to set email alerts
|

Pyro processing cement kiln bypass dust: Enhancing clinker phase formation

Abstract: The valorisation of cement kiln bypass dust (CBPD) is explored for sustainable production of cementitious clinker phases. CBPD can replace the calcareous component in cement manufacture and allow for a reduction in CO 2 emissions as the calcium component in CBPD is mostly decarbonised. CBPD was heated with/out the addition of alumina or silica at temperatures of 900 -1100°C to produce clinker phases. Belite and mayenite formed at temperatures as low as 900°C, while alite formation was achieved at 1200°C, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…As an example, the XRD pattern of AY7 is provided in Figure 8, where the characteristic peak of alite is observable at 14.9° 2θ. Alite is thermodynamically stable at 1250°C [52] but only practically forms at temperatures >1400°C [53], mineralisation by the presence of CaF2 has been reported to reduce its formation temperature [54,55], and similar mechanism may have occurred with chloride ions, as reported by Odler and Abdul-Maula [56] and Hanein et al [16]; a lowtemperature (around 1200°C) formation of C3S was also observed by Chen et al [57] using CaCl2 and CaSO4 as mineralizers for a more sustainable PC production. could not be co-produced, also suggesting their incompatibility under the assessed processing conditions.…”
Section: Angle (2θ)mentioning
confidence: 95%
See 1 more Smart Citation
“…As an example, the XRD pattern of AY7 is provided in Figure 8, where the characteristic peak of alite is observable at 14.9° 2θ. Alite is thermodynamically stable at 1250°C [52] but only practically forms at temperatures >1400°C [53], mineralisation by the presence of CaF2 has been reported to reduce its formation temperature [54,55], and similar mechanism may have occurred with chloride ions, as reported by Odler and Abdul-Maula [56] and Hanein et al [16]; a lowtemperature (around 1200°C) formation of C3S was also observed by Chen et al [57] using CaCl2 and CaSO4 as mineralizers for a more sustainable PC production. could not be co-produced, also suggesting their incompatibility under the assessed processing conditions.…”
Section: Angle (2θ)mentioning
confidence: 95%
“…As shown in Table 1, significant amounts of chloride and MgO are included in alinite cements; thus, this clinker phase is a good candidate in the CaO-SiO2-Al2O3-SO3-CaCl2-MgO system. The presence of chloride salt may also enhance the clinkering reactions by acting as a molten flux [13][14][15][16].…”
Section: Clinker Phases Of Interestmentioning
confidence: 99%
“…For decades, considerable efforts have been devoted to the environmentally-safe disposal and effective resource utilization of bypass dust [ [12] , [13] , [14] , [15] , [16] , [17] ]. Currently, the bypass dust is typically used as a blending material for cement or mortar in the production of hollow blocks, cement masonry, plastering mortar, and pavement bricks [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the cold end of a clinker kiln, dust is released (called aspiration dust), and its composition is similar to that of the initial raw mixture [ 36 ]. Clinker dust is generated in the last hot zone of the kiln, in the cooling sections, and in the clinker conveyor gallery [ 37 ]. It has been established that the production of each kilogram of clinker accounts for up to 7.5 m 3 of exhaust gases, with a dust content of up to 70 g/m 3 [ 38 ].…”
Section: Introductionmentioning
confidence: 99%